ENSURING YOUTH EMPLOYMENT AND PREVENTING CRIME AMONG THEM IS AN IMPORTANT COMPONENT OF THE YOUTH POLICY OF UZBEKISTAN (International journal of artificial intelligence, 2026)
This article covers youth policy in New Uzbekistan, large-scale reforms to ensure youth employment, youth infrastructures being created, negative situations and crimes being committed among young people, the conditions being created for them.The article examines issues such as increasing the socio-political activity of young people today, expanding their participation as much as possible in all political reforms taking place in society.Recommendations for the effective use of modern technologies have also been developed to spiritually and ideologically support the ideological immunity of young people.The article, having scientific and practical significance, will be the basis for the formation of a strategy for working with young people in the conditions of modern information technology.